Green low-cost sugar-based multifunctional carbon fiber and preparation method thereof
By directly introducing multifunctional phases in the preparation stage of carbon fiber raw wire, the problems of multifunctionalization and sustainable development of traditional carbon fibers are solved, and efficient and green multifunctional carbon fiber synthesis is achieved, with broad industrial application prospects.
Patent Information
- Application Number
- CN202510082262.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-20
AI Technical Summary
Traditional carbon fibers have limitations in terms of multifunctionalization, and it is difficult to directly introduce multifunctional phases in the preparation stage of the raw silk. They need to go through a complex later modification process, and the preparation process is complex and energy consumption is high. They rely on non-renewable fossil resources to affect environmental and resource consumption.
Water-soluble sugars, gel monomers, reinforced phases and spinning additives are used as raw materials to prepare carbon fiber raw filaments containing multifunctional phases in situ by wet spinning and drying, and efficient synthesis of multifunctional carbon fibers is achieved through pre-carbonization and carbonization treatment.
The multifunctional phase is directly introduced during the preparation stage of the raw silk, which simplifies the process, reduces energy consumption, and does not rely on non-renewable fossil resources. It has the advantages of green and environmental protection and simplified operation, which significantly improves the multifunctional performance of carbon fiber.
Smart Images

Figure CN119843392A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon fiber preparation, and specifically relates to a green, low-cost sugar-based multifunctional carbon fiber and a preparation method thereof. Background Art
[0002] Traditional carbon fiber has excellent properties such as high strength, high modulus, light weight, high temperature resistance and corrosion resistance. It is widely used in aerospace, automobile manufacturing, wind turbine blades, sports equipment and building reinforcement, and can significantly improve the structural performance and durability of the material.
[0003] However, traditional carbon fibers have significant limitations in terms of multifunctionality. It is difficult to directly introduce multifunctional phases in the precursor preparation stage. This can usually only be achieved by performing secondary functionalization treatment on the finished carbon fibers. This later modification process not only relies on toxic and hazardous substances, increasing the environmental burden, but also makes the process more complicated. In addition, the preparation process of traditional polyacrylonitrile (PAN)-based carbon fibers is complex and energy-intensive, requiring multiple steps of high-temperature carbonization, which limits production and costs. The emission of harmful gases during the preparation process and the difficulty of recycling also have an adverse impact on the environment. Moreover, the main raw materials of carbon fibers rely on non-renewable fossil resources, such as PAN and asphalt, which consume a lot of resources. The above problems limit the application potential of carbon fibers in multifunctional composite materials such as electrical conductivity, thermal conductivity, and energy storage, and new methods are urgently needed to promote their multifunctionality and sustainable development. Summary of the invention
[0004] The purpose of the present invention is to provide a green, low-cost sugar-based multifunctional carbon fiber and a preparation method thereof. By using water-soluble sugars, gel monomers, reinforcing phases and spinning aids as the main raw materials, carbon fiber precursors containing multifunctional phases are prepared in situ by wet spinning and drying, and then pre-carbonized and carbonized to achieve efficient synthesis of multifunctional carbon fibers. Compared with traditional carbon fibers that need to be functionalized in the later stage, the present invention can directly introduce reinforcing phases in the precursor preparation stage, so that the multifunctional phases are evenly distributed, significantly simplifying the process, reducing energy consumption, not relying on non-renewable fossil resources, and having the advantages of being green, environmentally friendly, and easy to operate.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention is to provide a method for preparing a green and low-cost sugar-based multifunctional carbon fiber, comprising the following steps:
[0007] Dissolving gel monomer, water-soluble sugar and cross-linking agent in water to obtain solution A; adding reinforcing phase, spinning aid, initiator and catalyst to the solution A to prepare spinning solution;
[0008] Prepare a solution identical to the solution A, add an ionic gelling agent, and use it as a coagulation bath;
[0009] Using a solution in which the gel monomer, the cross-linking agent, the reinforcing phase and the spinning aid in the spinning solution are omitted as the water bath solution;
[0010] Obtaining multifunctional carbon fiber precursor by wet spinning using the spinning solution, the coagulation bath and the water bath solution;
[0011] Pre-carbonizing the multifunctional carbon fiber precursor to obtain pre-carbonized multifunctional fibers; and then carbonizing the pre-carbonized multifunctional fibers to obtain the green, low-cost sugar-based multifunctional carbon fibers;
[0012] The reinforcing phase includes diamond, graphene, graphene oxide, carbon nanotubes, fullerene, silicon, boron, ZrO2, HfO2, Ta2O5, Al2O3 or TiO2.
[0013] The present invention uses water-soluble sugars, gel monomers, reinforcing phases and spinning aids as main raw materials, and prepares carbon fiber precursors containing multifunctional phases in situ through wet spinning and drying. The coagulation bath and water bath solutions prepared in the wet spinning process can be recycled multiple times. The present invention introduces a multifunctional reinforcing phase in the precursor preparation stage; then removes volatiles and moisture through pre-carbonization, promotes caramelization reaction, reduces internal stress, avoids cracking and breaking, completes stabilization treatment, ensures fiber uniformity and strength; and finally obtains multifunctional carbon fiber through carbonization.
[0014] Optionally, the gel monomer includes one or more of acrylamide, acrylic acid, methacrylic acid, polyethylene glycol diacrylate and N-isopropylacrylamide.
[0015] Optionally, the water-soluble sugar includes one or more of glucose, fructose, galactose, maltose, sucrose, lactose and oligofructose.
[0016] Optionally, the crosslinking agent includes one or more of N,N'-methylenebisacrylamide, ethylene glycol diacrylate, ethylene glycol dimethacrylate, diacrylamide ethylenediamine, polyethylene glycol diacrylate, trimethylolpropane triacrylate, divinyl urea, N,N'-ethylenebisacrylamide and N,N'-bis(acryloyloxyethyl)urea.
[0017] Preferably, the mass ratio of the gel monomer, the water-soluble sugar, the cross-linking agent and water in the solution A is 1-20:10-60:0.05-2:100.
[0018] Optionally, the spinning aid includes one or more of sodium alginate, sodium polyacrylate and sodium carboxymethyl cellulose.
[0019] Optionally, the initiator includes one or more of ammonium persulfate, azobisisobutyronitrile, potassium persulfate and hydrogen peroxide.
[0020] Optionally, the catalyst includes one or more of triethanolamine, sodium bisulfite and tetramethylethylenediamine.
[0021] Preferably, in the spinning solution, the reinforcing phase is added in the form of micro-nano powder or aqueous dispersion, and the spinning aid, initiator and catalyst are added in the form of aqueous solution, wherein the particle size of the reinforcing phase does not exceed 30 μm, the concentration of the reinforcing phase aqueous dispersion is 0.05-30wt.%, the concentration of the spinning aid aqueous solution is 1-10wt.%, the concentration of the initiator aqueous solution is 0.5-20wt.%, and the concentration of the catalyst aqueous solution is 0.5-20wt.%.
[0022] Preferably, in the spinning solution, the mass ratio of the reinforcing phase to the water in the solution A is 0.05 to 20:100, and the mass ratio of the spinning aid to the water in the solution A is 0.5 to 10:100.
[0023] In the spinning solution, the amount of initiator and catalyst added is determined by the amount of gel monomer used, and can be added according to the conventional amount in the art.
[0024] Optionally, the ionic gelling aid includes calcium chloride and / or calcium acetate.
[0025] Preferably, the ionic gelling agent accounts for 1-20% of the mass of the coagulation bath.
[0026] Preferably, during the wet spinning process, the temperature of the water bath solution is 25-90°C.
[0027] Preferably, in the wet spinning process, the process parameters are: spinning needle inner hole diameter 30-200 μm, spinning speed 50-2000 μL / min, drawing machine speed 1-20 m / min, drying temperature 50-300° C., and drying time 1-30 min.
[0028] Preferably, the pre-carbonization is performed by gradient heating, with the maximum temperature not exceeding 350°C.
[0029] More specific operating steps are: gradually heating the multifunctional carbon fiber precursor in a continuous pre-carbonization furnace, and evenly pulling it through each temperature zone to achieve stable pre-carbonization and obtain pre-carbonized fibers with uniform quality; the wire feeding speed is preferably 0.02-1 m / min to ensure that the fiber gradually adapts to the heating process to avoid damage to the internal structure, and the precursor has sufficient residence time in each temperature zone to react and form an ideal micro-nano structure.
[0030] Preferably, the carbonization is carried out under anaerobic conditions, with the temperature being directly or gradually increased to 800-2000° C., with a heating rate of 1-20° C. / min, and the holding time of each gradient being 0.5-6 h.
[0031] The second technical solution of the present invention is to provide a green, low-cost, sugar-based multifunctional carbon fiber prepared according to the above-mentioned method for preparing the green, low-cost, sugar-based multifunctional carbon fiber.
[0032] The third technical solution of the present invention is to provide a multifunctional graphite fiber obtained by graphitizing the pre-carbonized multifunctional fiber or the green low-cost sugar-based multifunctional carbon fiber prepared according to the above preparation method.
[0033] Preferably, the graphitization temperature is 2000-3000° C., the heating rate is 0.5-20° C. / min, and the holding time is 0.5-6 h.
[0034] The beneficial technical effects of the present invention are as follows:
[0035] The present invention aims at the problems of long cycle, complex process, high energy consumption, large pollution and strong dependence on non-renewable fossil resources in the traditional carbon fiber preparation process, and innovatively proposes a method for preparing carbon fiber by directly introducing a multifunctional phase in the precursor preparation stage. The method uses water-soluble sugars, gel monomers, reinforcing phases and spinning aids as raw materials, adopts wet spinning to prepare precursors containing multifunctional phases, and through pre-carbonization and carbonization steps, realizes the efficient synthesis of multifunctional carbon fibers. These multifunctional phases give carbon fibers excellent properties such as high temperature resistance, oxidation resistance, corrosion resistance, high strength, high electrical conductivity, high thermal conductivity and high specific surface area, making it expected to be applied in aerospace, automotive industry, electronic equipment, energy field, construction engineering, medical equipment and environmental protection and other fields. The method provided by the present invention not only has a simple process flow, low energy consumption and low environmental burden, but also ensures the uniform distribution of the multifunctional phase, showing the advantages of green environmental protection and easy operation, and has broad industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 Continuous collection production line for wet spinning.
[0037] Figure 2 This is a picture of the continuous pre-carbonization furnace used in the embodiments of the present invention.
[0038] Figure 3 It is a device for carbonization or graphitization in the embodiment of the present invention.
[0039] Figure 4 This is the temperature zone setting diagram of the continuous pre-carbonization furnace in Examples 1 and 3.
[0040] Figure 5This is the temperature zone setting diagram of the continuous pre-carbonization furnace in Example 2.
[0041] Figure 6 This is a picture of the diamond-reinforced carbon fiber prepared in Example 1.
[0042] Figure 7 This is a TEM image of the diamond-reinforced carbon fiber prepared in Example 1.
[0043] Figure 8 This is a graph showing the tensile strength of the diamond-reinforced carbon fiber prepared in Example 1.
[0044] Fig. 9 These are the oxidation resistance test results of the high temperature resistant and oxidation resistant graphite fiber prepared in Example 3. DETAILED DESCRIPTION
[0045] Now, various exemplary embodiments of the present invention are described in detail, which should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0046] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0047] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0048] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0049] The wet spinning continuous collection production line in the embodiment of the present invention is shown in Figure 1 .
[0050] The picture of the continuous pre-carbonization furnace used in the embodiment of the present invention is shown in Figure 2 .
[0051] The equipment for carbonization or graphitization in the embodiment of the present invention is shown in Figure 3 .
[0052] Example 1
[0053] (1) Preparation of spinning solution: First, 12 g of acrylic acid, 40 g of glucose and 0.5 g of ethylene glycol diacrylate were mixed and dissolved in 110 mL of deionized water, and stirred to form a uniform transparent solution. Then, 48 g of 5% diamond water dispersion was added, and the diamond particle size was 10 nm. 50 mL of 4% sodium alginate aqueous solution, 4 mL of 10% ammonium persulfate aqueous solution, and 4 mL of 10% tetramethylethylenediamine aqueous solution were added. Ultrasonication and stirring were performed to form a uniform solution. The bubbles in the spinning solution were removed by a debubbler to obtain a spinning solution for standby use.
[0054] (2) Preparation of coagulation bath: 1800 g of acrylic acid, 6000 g of glucose, 150 g of ethylene glycol diacrylate, and 1800 g of calcium chloride are mixed and dissolved in 16500 mL of deionized water, and stirred in a coagulation bath to form a uniform transparent solution. During the spinning operation, the circulation pump of the coagulation bath is turned on to circulate the coagulation bath in a directional manner in the coagulation bath. In addition, the coagulation bath can be recycled multiple times after preparation.
[0055] (3) Preparation of water bath solution: 6000 g of glucose, 600 mL of 10% by mass ammonium persulfate aqueous solution, and 600 mL of 10% by mass tetramethylethylenediamine aqueous solution are mixed and dissolved in 16500 mL of deionized water, and stirred in a constant temperature water bath to form a uniform transparent solution. During the spinning operation, the heating device of the constant temperature water bath is turned on to stabilize the temperature of the water bath at 70° C. In addition, the water bath solution can be recycled many times after preparation.
[0056] (4) Preparation of carbon fiber precursor: Use a syringe to absorb the prepared spinning solution and connect the spinning needle. The inner diameter of the spinning needle is 80μm. Then use a high-precision injection pump to inject the spinning solution into the coagulation bath through the spinning needle at a speed of 500μL / min to generate gel fiber. After the gel fiber is pulled by a drawing machine, it passes through a 70℃ constant temperature water washing tank, the drawing machine speed is 8m / min, and it enters a 120℃ blast dryer for drying. Finally, it is collected into bundles by a collection roller to obtain carbon fiber precursor.
[0057] (5) Pre-carbonization: The carbon fiber precursor is passed through a continuous pre-carbonization furnace at a speed of 0.05 m / min through a wire unwinding machine and a traction machine. The precursor is pulled through each temperature zone in a uniform manner to achieve stable pre-carbonization and obtain pre-carbonized fibers of uniform quality. The pre-carbonization production line adopts a 5-section furnace design, each furnace section has 5 temperature zones, a total of 25 temperature zones, gradually increasing from 25°C to 220°C. The temperature zones are distributed from low temperature, medium temperature to high temperature, gradually removing volatiles and moisture, promoting caramelization reaction, and completing the final stabilization treatment to ensure fiber uniformity and strength. See the temperature zone setting of the continuous pre-carbonization furnace for details. Figure 4 .
[0058] (6) Carbonization: The pre-carbonized fibers were carbonized in a carbonization furnace. Under vacuum conditions, the temperatures were raised to 360°C, 920°C, 1050°C, and 1400°C at a heating rate of 4°C / min, and each temperature was kept for 2 h. The furnace was then cooled to room temperature to obtain diamond-reinforced carbon fibers.
[0059] (7) Graphitization: The multifunctional carbon fiber was graphitized in a graphitization furnace. Under vacuum conditions, the temperature was increased to 1800°C at a heating rate of 4°C / min, and then increased to 2800°C at a heating rate of 2°C / min. The temperature was kept at this temperature for 2 h, and the furnace was cooled to room temperature to obtain diamond-reinforced graphite fiber.
[0060] The picture of diamond-reinforced carbon fiber prepared in Example 1 is shown in Figure 6 .
[0061] The TEM image of the diamond-reinforced carbon fiber prepared in Example 1 is shown in Figure 7 .
[0062] from Figure 7 As can be seen in the figure, this is a transmission electron microscope (TEM) image of diamond-reinforced carbon fiber, which clearly shows the microstructural characteristics of the sample. Two significant areas can be observed in the image: the ordered lattice fringes represent the diamond phase, while the matrix is mainly composed of nanocrystalline graphite and amorphous carbon. The lattice fringes of the diamond phase are clear and regular, indicating that it is highly crystallized and has extremely high structural stability; while the matrix part shows a relatively disordered feature, reflecting the random distribution of amorphous carbon and nanocrystalline graphite. In addition, the inset is a selected area electron diffraction (SAED) pattern, showing a combination of discrete spots and continuous rings, where the spots correspond to the highly ordered crystal features of the diamond phase, while the continuous rings reflect the presence of amorphous carbon and nanocrystalline graphite.
[0063] The tensile strength of the diamond-reinforced carbon fiber prepared in Example 1 is shown in FIG. Figure 8 , wherein 1#, 2#, and 3# are respectively the tensile strengths of different segments of the diamond-reinforced carbon fiber prepared in Example 1.
[0064] Example 2
[0065] (1) Preparation of spinning solution: First, 36 g of methacrylic acid, 120 g of sucrose and 3 g of N,N'-methylenebisacrylamide were mixed and dissolved in 330 mL of deionized water, and stirred to form a uniform transparent solution. Then, 72 g of 5% boron aqueous dispersion with a boron particle size of 10 nm was added, 120 mL of 5% sodium alginate aqueous solution, 12 mL of 10% azobisisobutyronitrile aqueous solution, and 12 mL of 10% sodium bisulfite aqueous solution were added, and ultrasonic and stirring were performed to form a uniform solution. The bubbles in the spinning solution were removed by a defoamer to obtain a spinning solution for standby use.
[0066] (2) Preparation of coagulation bath: 1800 g of methacrylic acid, 6000 g of sucrose, 150 g of N,N'-methylenebisacrylamide, and 1800 g of calcium chloride are mixed and dissolved in 16500 mL of deionized water, and stirred in a coagulation bath to form a uniform transparent solution. During the spinning operation, the circulation pump of the coagulation bath is turned on to circulate the coagulation bath in a directional manner in the coagulation bath. In addition, the coagulation bath can be recycled multiple times after preparation.
[0067] (3) Prepare a water bath solution: 6000 g of sucrose, 600 mL of a 10% by mass aqueous solution of azobisisobutyronitrile, and 600 mL of a 10% by mass aqueous solution of sodium bisulfite are mixed and dissolved in 16500 mL of deionized water, and stirred in a constant temperature water bath to form a uniform transparent solution. During the spinning operation, the heating device of the constant temperature water bath is turned on to stabilize the temperature of the water bath at 60° C. In addition, the prepared water bath solution can be recycled for multiple times.
[0068] (4) Preparation of carbon fiber precursor: Use a syringe to absorb the prepared spinning solution and connect the spinning needle. The inner diameter of the spinning needle is 60μm. Then use a high-precision injection pump to inject the spinning solution into the coagulation bath through the spinning needle at a speed of 400μL / min to generate gel fiber. The gel fiber is pulled by a drawing machine and passed through a 60℃ constant temperature water washing tank. The drawing machine speed is 8m / min, and it enters a 90℃ blast dryer for drying. Finally, it is collected into bundles by a collection roller to obtain carbon fiber precursor.
[0069] (5) Pre-carbonization: The carbon fiber precursor is passed through a continuous pre-carbonization furnace at a speed of 0.1m / min through a wire unwinding machine and a traction machine. The precursor is pulled through each temperature zone in a uniform manner to achieve stable pre-carbonization and obtain pre-carbonized fibers of uniform quality. The pre-carbonization production line adopts a 5-section furnace design, each furnace section has 5 temperature zones, a total of 25 temperature zones, gradually increasing from 25°C to 220°C. The temperature zones are distributed from low temperature, medium temperature to high temperature, gradually removing volatiles and moisture, promoting caramelization reaction, and completing the final stabilization treatment to ensure fiber uniformity and strength. See the temperature zone setting of the continuous pre-carbonization furnace for details. Figure 5 .
[0070] (6) Carbonization: The pre-carbonized fibers were carbonized in a carbonization furnace. Under argon conditions, the temperature was raised to 1400°C at a heating rate of 2°C / min, and the temperature was kept at that temperature for 2 h. The furnace was then cooled to room temperature to obtain highly conductive carbon fibers.
[0071] (7) Graphitization: The highly conductive carbon fibers were graphitized using a graphitization furnace. Under argon conditions, the temperature was increased to 1800°C at a heating rate of 8°C / min, and then increased to 2600°C at a heating rate of 4°C / min. The temperature was maintained for 3 h and the furnace was cooled to room temperature to obtain highly conductive graphite fibers.
[0072] The conductivity of the highly conductive carbon fiber prepared in Example 2 is 1.1×10 5 S / m.
[0073] Example 3
[0074] (1) Preparation of spinning solution: First, 12 g of acrylic acid, 40 g of glucose and 0.5 g of ethylene glycol diacrylate were mixed and dissolved in 110 mL of deionized water, and stirred to form a uniform transparent solution. Then, 48 g of 5% zirconium oxide aqueous dispersion, 50 mL of 4% sodium alginate aqueous solution, 4 mL of 10% ammonium persulfate aqueous solution, and 4 mL of 10% tetramethylethylenediamine aqueous solution were added, and ultrasonic and stirring were performed to form a uniform solution. The bubbles in the spinning solution were removed by a debubbler to obtain a spinning solution for standby use.
[0075] (2) Preparation of coagulation bath: 1800 g of acrylic acid, 6000 g of glucose, 150 g of ethylene glycol diacrylate, and 1800 g of calcium chloride are mixed and dissolved in 16500 mL of deionized water, and stirred in a coagulation bath to form a uniform transparent solution. During the spinning operation, the circulation pump of the coagulation bath is turned on to circulate the coagulation bath in a directional manner in the coagulation bath. In addition, the coagulation bath can be recycled multiple times after preparation.
[0076] (3) Preparation of water bath solution: 6000 g of glucose, 600 mL of 10% by mass ammonium persulfate aqueous solution, and 600 mL of 10% by mass tetramethylethylenediamine aqueous solution are mixed and dissolved in 16500 mL of deionized water, and stirred in a constant temperature water bath to form a uniform transparent solution. During the spinning operation, the heating device of the constant temperature water bath is turned on to stabilize the temperature of the water bath at 70° C. In addition, the water bath solution can be recycled many times after preparation.
[0077] (4) Preparation of carbon fiber precursor: Use a syringe to absorb the prepared spinning solution and connect the spinning needle. The inner diameter of the spinning needle is 80μm. Then use a high-precision injection pump to inject the spinning solution into the coagulation bath through the spinning needle at a speed of 500μL / min to generate gel fiber. After the gel fiber is pulled by a drawing machine, it passes through a 70℃ constant temperature water washing tank, the drawing machine speed is 8m / min, and it enters a 120℃ blast dryer for drying. Finally, it is collected into bundles by a collection roller to obtain carbon fiber precursor.
[0078] (5) Pre-carbonization: The carbon fiber precursor is passed through a continuous pre-carbonization furnace at a speed of 0.05 m / min through a wire unwinding machine and a traction machine. The precursor is pulled through each temperature zone in a uniform manner to achieve stable pre-carbonization and obtain pre-carbonized fibers of uniform quality. The pre-carbonization production line adopts a 5-section furnace design, each furnace section has 5 temperature zones, a total of 25 temperature zones, gradually increasing from 25°C to 220°C. The temperature zones are distributed from low temperature, medium temperature to high temperature, gradually removing volatiles and moisture, promoting caramelization reaction, and completing the final stabilization treatment to ensure fiber uniformity and strength. See the temperature zone setting of the continuous pre-carbonization furnace for details. Figure 4 .
[0079] (6) Graphitization: The pre-carbonized fiber was graphitized in a graphitization furnace. Under vacuum conditions, the temperature was increased to 1800°C at a heating rate of 4°C / min, and then increased to 2800°C at a heating rate of 2°C / min. The temperature was kept at this temperature for 3 h and the furnace was cooled to room temperature to obtain high temperature resistant and oxidation-resistant graphite fiber.
[0080] The oxidation resistance test results of the high temperature resistant and oxidation resistant graphite fiber prepared in Example 3 are shown in Fig. 9 .
[0081] from Fig. 9 As can be seen in the figure, the test results of the oxidation resistance of zirconia reinforced graphite fiber are shown, including the relationship curves of the sample's mass loss (Weight%), differential thermogravimetric (DTG% / min) and heat flow (Heat flow W / g) as a function of temperature. The mass loss curve (black) shows that the starting temperature of the sample's oxidation is 764°C, at which time the sample begins to experience significant mass loss. The DTG curve (red) shows the maximum rate point of the oxidation reaction, indicating that the oxidation reaction is most intense within this temperature range. The heat flow curve (blue) shows an obvious exothermic process (Exothermic), further indicating that the oxidation reaction of the sample is an exothermic reaction. From Fig. 9 It can be seen that the oxidation onset temperature of 764°C indicates that the oxidation resistance of graphite fiber is significantly improved, which may be due to the reinforcement of zirconia. Zirconia can form a protective oxide coating on the fiber surface, inhibiting the penetration of oxidants, thereby delaying the oxidative decomposition of graphite fiber. The overall results show that zirconia-reinforced graphite fiber exhibits excellent antioxidant properties in high temperature environments and is very suitable for special engineering applications that require high temperature resistance and antioxidant properties.
[0082] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing green and low-cost sugar-based multifunctional carbon fiber, characterized in that: The following steps are involved: Dissolving gel monomer, water-soluble sugar and cross-linking agent in water to obtain solution A; Adding a reinforcing phase, a spinning aid, an initiator and a catalyst into the solution A to prepare a spinning solution; Prepare a solution identical to the solution A, add an ionic gelling agent, and use it as a coagulation bath; Using a solution in which the gel monomer, the cross-linking agent, the reinforcing phase and the spinning aid in the spinning solution are omitted as the water bath solution; Obtaining multifunctional carbon fiber precursor by wet spinning using the spinning solution, the coagulation bath and the water bath solution; Pre-carbonizing the multifunctional carbon fiber precursor to obtain pre-carbonized multifunctional fibers; and then carbonizing the pre-carbonized multifunctional fibers to obtain the green, low-cost sugar-based multifunctional carbon fibers; The reinforcing phase includes diamond, graphene, graphene oxide, carbon nanotubes, fullerene, silicon, boron, ZrO2, HfO2, Ta2O5, Al2O3 or TiO2.
2. The method for preparing green, low-cost sugar-based multifunctional carbon fibers according to claim 1, characterized in that: The mass ratio of the gel monomer, the water-soluble sugar, the cross-linking agent and water in the solution A is 1-20:10-60:0.05-2:
100.
3. The method for preparing green, low-cost sugar-based multifunctional carbon fibers according to claim 1, characterized in that: In the spinning solution, the reinforcing phase is added in the form of micro-nano powder or aqueous dispersion, and the spinning aid, initiator and catalyst are added in the form of aqueous solution, wherein the particle size of the reinforcing phase does not exceed 30 μm, the concentration of the reinforcing phase aqueous dispersion is 0.05-30wt.%, the concentration of the spinning aid aqueous solution is 1-10wt.%, the concentration of the initiator aqueous solution is 0.5-20wt.%, and the concentration of the catalyst aqueous solution is 0.5-20wt.%.
4. The method for preparing green and low-cost sugar-based multifunctional carbon fiber according to claim 1, characterized in that: In the spinning solution, the mass ratio of the reinforcing phase to the water in the solution A is 0.05 to 20:100, and the mass ratio of the spinning aid to the water in the solution A is 0.5 to 10:
100.
5. The method for preparing green and low-cost sugar-based multifunctional carbon fiber according to claim 1, characterized in that: The ionic gelling agent accounts for 1 to 20% of the mass of the coagulation bath.
6. The method for preparing green and low-cost sugar-based multifunctional carbon fiber according to claim 1, characterized in that: In the wet spinning process, the process parameters are: the inner hole diameter of the spinning needle is 30-200 μm, the spinning speed is 50-2000 μL / min, the drawing machine speed is 1-20 m / min, the drying temperature is 50-300° C., and the drying time is 1-30 min.
7. The method for preparing green and low-cost sugar-based multifunctional carbon fiber according to claim 1, characterized in that: The pre-carbonization is performed by gradient heating, and the maximum temperature does not exceed 350°C.
8. The method for preparing green and low-cost sugar-based multifunctional carbon fiber according to claim 1, characterized in that: The carbonization is carried out under anaerobic conditions, and the temperature is directly or gradually increased to 800-2000° C., the heating rate is 1-20° C. / min, and the insulation time of each gradient is 0.5-6h.
9. A green, low-cost sugar-based multifunctional carbon fiber prepared according to the method for preparing green, low-cost sugar-based multifunctional carbon fiber according to any one of claims 1 to 8.
10. A multifunctional graphite fiber, characterized in that: The method is obtained by graphitizing the pre-carbonized multifunctional fiber or the green low-cost sugar-based multifunctional carbon fiber prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of double-net hydrogel fiber and product thereof
CN104652119A
Cutting-resistant graphene modified carbon fiber filament and preparation method thereof
CN113445158A
Carbon complexed fiber and method of producing the same
KR1020160150456A
Cited By
Wear-resistant puncture-proof butyronitrile glove and preparation method thereof
CN120737458A
A puncture-resistant and abrasion-resistant nitrile glove and a method of making the same
CN120737458B